The Improvement of Suroboyo Bus Public Transportation Services Based on the Bus Golek Application Innovation in the City of Surabaya Indonesia - Diana, Diana Hertati; Lukman, Arif (Archives of Business Research, 2021)
One of the government's duties to fulfill the need for safe, comfortable and affordable public transportation services so as to facilitate the mobilization of the community in carrying out its activities is the Golek Bus Application Service as an innovation in improving public transportation services for users of the Suroboyo Bus service. The purpose of this research is to find out and describe the application innovation Gobis in improving public transportation services Suroboyo Bus in the city of Surabaya by using qualitative research methods with data collection techniques observation, interviews, and documentation. Data analysis techniques are data collection, data condensation, data presentation, and drawing conclusions. The results show that the five attributes of innovation are as follows: 1) Relative advantage in innovation has been carried out optimally because it has advantages over previous innovations, 2) Conformity in the innovation of gobis applications in suroboyo bus services is optimal, but there are still some that need improvement due to the lack of additional routes for lines that match the corridors in the gobis application, 3) The complexity of this new innovation is also good but there are still shortcomings related to the arrival and departure schedules of Suroboyo Bus.